On-Going Russo-Ukrainian War and Advancing Forensic Medical Services: Addressing Critical Challenges - Natalia Kozan; Yuliia Kotsiubynska; Ihor Onyshchuk; Ihor Ivaskevych; Valeriia Chadiuk (Galician Medical Journal)
Russia’s full-scale invasion of Ukraine, launched on February 24, 2022, has caused profound global disruptions, including social and humanitarian crises, economic instability, and significant geopolitical transformations. While these direct effects are widely discussed, indirect influences extend across multiple domains, such as legal frameworks, migration, media narratives, and public policy. Despite significant attention to political and humanitarian aspects, the impact on healthcare systems remains underexplored. In addition, forensic medical services, positioned at the intersection of healthcare and law, remain insufficiently addressed. Thus, this letter aims to draw attention to forensic medical services, discuss their key systemic limitations, propose a pilot education initiative, and outline essential steps to align practices with international standards.